Pemikiran Bung Karno dan Fatima Mernissi Tentang Emansipasi Perempuan dan Relevansinya terhadap Hak dan Kewajiban Suami-Istri dalam Hukum Keluarga Islam - Bahrul Ulum; Khofi (Kartika: Jurnal Studi Keislaman, 2026)
This study analyzes the relevance of the thoughts of Bung Karno and Fatima Mernissi regarding the rights and obligations of husbands and wives in Islamic family law in Indonesia, as well as their contribution to the development of a more just family law paradigm. Using a qualitative library research approach with comparative analysis of the works of both figures and literature on Islamic family law and gender justice. The findings show that both figures share the same orientation in realizing fair and dignified relations between men and women, albeit through different approaches. Bung Karno views women's emancipation as part of the national struggle against oppression and for national strengthening, while Fatima Mernissi emphasizes the importance of reinterpreting Islamic teachings to correct patriarchal interpretations that are inconsistent with Islamic principles of justice. The synthesis of both thoughts produces a conceptual framework that positions the husband-wife relationship as a partnership based on deliberation, shared responsibility, respect for each other's rights, and orientation toward family well-being (maslahah). The study concludes that the development of Islamic family law in Indonesia should be directed toward strengthening substantive justice without ignoring the principles of sharia. The novelty of this research lies in the integration of Bung Karno and Fatima Mernissi's thoughts as a conceptual foundation for reforming Islamic family law to be more contextual, responsive, and oriented toward achieving the objectives of Islamic family law